(untitled) (Journal of Pathology of Nepal, 2015)
Warthin tumor is the second most common salivary gland tumor affecting male in 6th to 7th decade of life. It can grow in peri- parotid or cervical lymph nodes too. Preoperative FNAC procedure can induce partial to near total infarction and metaplastic changes in tumor masquerading with malignancy, mainly squamous cell carcinoma or low grade mucoepidermoid carcinoma. Here, I present a case in which FNAC procedure was performed. Later on histopathology, metaplastic changes in epithelium of Warthin tumor and extensive infarction were noted. Such lesion could have been mistaken as Squamous cell carcinoma or low grade mucoepidermoid carcinoma. Thus acquaintance with morphological alteration caused by FNAC procedure is very important to avoid misdiagnosis. Journal of Pathology of Nepal (2015) Vol. 5, 778-780